Using Asymmetric Dominance to Resolve Toxic Debt: Combining Online and Field Experiments. Issue 4 (14th December 2021) - Anderson, Jackson T.; Luchtenberg, Kimberly F.; Seiler, Michael J.
Abstract: This study employs a behavioral technique known as asymmetric dominance used to nudge defaulted borrowers toward a repayment option that is in their best interest (lowest implied APR) while at the same time encouraging greater repayment, resulting in a win-win for both lenders and borrowers. We demonstrate the efficacy of this approach through an online experiment and then through a field experiment of 1st- and 2nd-lien actual defaulted mortgage pools. We address the generalization of asymmetric dominance by documenting success across multiple consumer asset classes – mortgages, auto loans, payday loans, student loans, health care debt and credit card debt. Finally, our results hold across 2-, 3-, and 4-digit monthly repayment amounts.